Prevalence and determinants of loneliness in people living with dementia: Findings from the IDEAL programme. (21st April 2020) - Victor, Christina R.; Rippon, Isla; Nelis, Sharon M.; Martyr, Anthony; Litherland, Rachael; Pickett, James; Hart, Nicola; Henley, Josie; Matthews, Fiona; Clare, Linda; ,
Abstract : Objective: To establish the prevalence and determinants of loneliness among people living with dementia. Methods: Using data from the baseline wave of the Improving the experience of Dementia and Enhancing Active Life (IDEAL) cohort study, we examined the prevalence and predictors of loneliness in 1547 people with mild‐to‐moderate dementia. Loneliness was assessed using the six‐item De Jong Gierveld loneliness scale. Results: About 30.1% of people with dementia reported feeling moderately lonely and 5.2% severely lonely. Depressive symptoms and increased risk of social isolation were associated with both moderate and severe loneliness. Those living alone were more likely to experience severe loneliness as were those reporting poorer quality of life. Marital status was not associated with loneliness nor were dementia diagnosis or cognitive function. Conclusions: This is one of the few large‐scale studies to explore the prevalence of and determinants of loneliness among people living with dementia. Social isolation, depression and living alone were associated with experiencing loneliness. Longitudinal studies are needed to determine the directionality of these associations.